2016
DOI: 10.1371/journal.pone.0163056
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Evaluation Does Not Improve Endoscopic Ultrasound-Guided Fine Needle Aspiration Adequacy in Pancreatic Masses: A Meta-Analysis and Systematic Review

Abstract: Background and ObjectivesRapid on-site evaluation (ROSE) during endoscopic ultrasonography-guided fine needle aspiration (EUS–FNA) of pancreatic masses has been reported to be associated with improved adequacy and diagnostic yield. However, recent observational data on the impact of ROSE have reported conflicting results. A meta-analysis and systematic review was therefore conducted to evaluate the contribution of ROSE during EUS-FNA of pancreatic masses.MethodA systematic search was conducted in MEDLINE/Pubme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 32 publications
3
66
0
Order By: Relevance
“…These findings are consistent with a recent observation that a greater number of FNA passes may be required to achieve high diagnostic sensitivity from small pancreatic masses . The presence of ROSE was not associated with a higher rate of tissue adequacy for tumor profiling, which is concordant with a recent meta‐analysis of seven studies including 1299 patients that demonstrated no improvement in diagnostic yield, tissue adequacy rates, pooled sensitivity, or pooled sensitivity with ROSE for EUS‐FNA of pancreatic masses …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with a recent observation that a greater number of FNA passes may be required to achieve high diagnostic sensitivity from small pancreatic masses . The presence of ROSE was not associated with a higher rate of tissue adequacy for tumor profiling, which is concordant with a recent meta‐analysis of seven studies including 1299 patients that demonstrated no improvement in diagnostic yield, tissue adequacy rates, pooled sensitivity, or pooled sensitivity with ROSE for EUS‐FNA of pancreatic masses …”
Section: Discussionsupporting
confidence: 90%
“…12 The presence of ROSE was not associated with a higher rate of tissue adequacy for tumor profiling, which is concordant with a recent meta-analysis of seven studies including 1299 patients that demonstrated no improvement in diagnostic yield, tissue adequacy rates, pooled sensitivity, or pooled sensitivity with ROSE for EUS-FNA of pancreatic masses. 13 Liquid cytology samples, including FNA rinse material, have been demonstrated to be adequate for genomic testing in institutions that have validated these types of samples. 5,[14][15][16] In a prior study from our institution, adequate material was obtained for genomic testing from residual FNA rinse or FNA-acquired body fluid specimens in all 17 cases when tumor cellularity was ≥ 10% in the aspirate.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic focal lesions still represent the main indication with 80–94% sensitivity and up to 100% specificity . Rapid onsite evaluation has been introduced with up to a 15% gain in accuracy reducing the number of needle passes …”
Section: Interventional Eus: New Tools New (And Old) Applicationsmentioning
confidence: 99%
“…[33][34][35][36][37][38] Rapid onsite evaluation has been introduced with up to a 15% gain in accuracy 39 reducing the number of needle passes. [40][41][42][43] Endoscopic ultrasonography-guided tissue acquisition can be carried out by FNA and FNB, which typically use a core biopsy needle (Fig. 2).…”
Section: Fusion Imagingmentioning
confidence: 99%
“…A meta-analysis of seven studies (one randomized) with a total of 1299 patients, comparing EUS-FNAC with and without ROSE, concluded that ROSE did not make a significant difference to cytological adequacy or diagnostic yield [11]. Although overall the number of needle passes was similar in the two groups, in the one study which was randomized, seven passes were made for cytology in the absence of ROSE compared to four passes in the presence of ROSE [12].…”
mentioning
confidence: 99%